Evolution of cell-mediated immune defences: cloning and structural characterisation of the T cell receptor beta chain from the icefish Chionodraco hamatus (Perciformes: Channichthyidae) - Buonocore, Francesco; Randelli, Elisa; Viviana, Scala; Belardinelli, Maria Cristina; Casani, Daniela; Facchiano, Angelo M.; Costantini, Susan; Scapigliati, Giuseppe (Italian Journal of Zoology, 2009)
L'articolo è disponibile sul sito dell'editore http://www.tandfonline.com/ Studies on the immune defence system of Antarctic fishes are of interest to investigate the presence of evolutionary adaptations to low temperature seawater. In the present paper, primers designed to conserved regions of TR , the antigen receptor expressed by T lymphocytes and mediator of main adaptive immune responses, were used for the homology cloning of the icefish Chionodraco hamatus TR  chain cDNA. The full length cDNA consists of 1219 nucleotides that translates in a single reading frame to give a predicted 304-amino acid molecule. The sequence shows highest nucleotide and amino acid identity with the sea bream (Sparus aurata) TR  . A multiple alignment with other known TR  molecules evidenced the presence of conserved amino acid residues involved in structural and functional domains within most teleost species. Real-time PCR analysis was used to investigate TR  basal expression, that resulted maximal in the thymus, followed by gills and spleen. Finally, the 3D structure of the icefish TR  was predicted by homology modelling and compared to the closest homologous Sparus aurata, a fish Teleost living in more temperate environmental conditions. The comparison of these two models suggests that the icefish TR  may be more flexible, as a consequence of a less compact structure and a lower number of H-bonds.